Hypervalent Iodine-Mediated Synthesis of Steroidal 5/5-Spiroiminals - Rayala Naveen Kumar; Seongmin Lee (Molecules)
The hypervalent iodine-mediated formation of steroidal 5/5-spiroiminals and 5/5-spiroaminals from steroidal amines is presented. Under the influence of excess PhI(OAc)2 and iodine in acetonitrile at 0 °C, steroidal amines smoothly underwent cyclization to give a mixture of 5/5-spiroiminals and 5/5-spiroaminals. This reaction represents the first example of a C-H-activation-mediated formation of a spiroiminal. Presumably, the formation of 5/5-spiroiminals occurs through aminyl radical-mediated cyclization followed by amine-to-imine oxidation.